2011
DOI: 10.1108/14684521111127998
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of online users' keyword ads search behaviours

Abstract: Purpose -This paper intends to examine the antecedents of perceived creativity and flow experience in order to understand how consumers' advertisement keywords browsing influences their searching intentions and/or behaviours regarding purchase. In addition, it aims to consider two kinds of intentions in the theory of planned behaviour (TPB) to facilitate the translation of intentions into behaviour. Design/methodology/approach -Research constructs were drawn from pre-validated measurement items. An online surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…In Hoffman and Novak (1996), flow experience is conceptualised to deepen one's behavioural control and positive behaviour in interactions. In researching the keyword search behaviours of online users, Wu, Lin, and Lin (2011) found that flow experience indirectly affects behavioural control through controllability and self-efficacy. Taken together, we posit the following relationship:…”
Section: Causal Relationshipsmentioning
confidence: 99%
“…In Hoffman and Novak (1996), flow experience is conceptualised to deepen one's behavioural control and positive behaviour in interactions. In researching the keyword search behaviours of online users, Wu, Lin, and Lin (2011) found that flow experience indirectly affects behavioural control through controllability and self-efficacy. Taken together, we posit the following relationship:…”
Section: Causal Relationshipsmentioning
confidence: 99%
“…Other some studies, again, showed there is no significant relationship between subjective norm and intention (Davis et al, 1989;Mathieson, 1991;Chau & Hu, 2001;Lewis et al, 2003). Latest studies found that subjective was a predictor of intention at different areas (Alam & Sayuti, 2011;Gupta & Ogden, 2009;Iakovleva et al, 2011;Wu et al, 2011). Koklič and Vida (2009) External factors of the purchaser also influence the purchasing process of a custom-made prefabricated house.…”
Section: Subjective Normmentioning
confidence: 99%
“…Control beliefs are a person's beliefs toward factors available which facilitate or prevent performing a behavior (Ajzen, 2001;Tonglet et al, 2004). Latest studies found that perceived behavioral control was a predictor of intention (Iakovleva et al, 2011;Wu et al, 2011;Alam & Sayuti, 2011). Various research in various areas, showed that there is a positive relationship between perceived behavioral control and intention (Blanchard et al, 2008;Fang, 2006;Gopi & Ramayah, 2007;Ing-Long & Jian-Liang, 2005;Jen-Ruei et al, 2006;Mathieson, 1991;Ramayah et al, 2008;Shih & Fang, 2004;Taylor & Todd, 1995;Teo & Pok, 2003;Wise et al, 2006;Baker et al, 2007;Teo & Lee, 2010).…”
Section: Perceived Behavioral Controlmentioning
confidence: 99%
“…The Web provides fast and convenient access to information on an increasing range of local and global products and services (Ducoffe, 1996). Web keyword advertising ensures that marketing messages are targeted at users when they are searching for information on particular products or services, thereby enhancing the relevance of the advertising information (Ducoffe, 1996;Wu, Lin & Lin, 2011). Furthermore, the flexibility of Web advertising enables fast and frequent updating of information contained therein (Ducoffe, 1996).…”
Section: Problem Statementmentioning
confidence: 99%